Pemanfaatan Teknologi Dehidrator dan Pemasaran Digital untuk Meningkatkan Pendapatan Petani Lemon di Kecamatan Cihaurbeuti, Kabupaten Ciamis - Nurul Risti Mutiarasari; Andri Ulus Rahayu; Visi Tinta Manik (Universitas Islam Sumatera Utara, 2025)
The implementation of the Community Empowerment Program in Cihaurbeuti District, Ciamis Regency, aimed to increase the economic value of lemons through processing technology and digital marketing. This program was designed to address key issues, such as price fluctuations and the lack of post-harvest technology, which often leads to lemon spoilage. The proposed solution involved using an electric dehydrator to process lemons into dried lemon, which has a longer shelf life and higher market value. Additionally, digital marketing training was provided to help farmers expand their market reach and promote their products through online platforms. The training covered the use of marketplaces, branding strategies, and packaging to enhance product competitiveness. As a result, farmers showed significant improvements in their knowledge and skills: 83.3% in operating the dehydrator, 81.9% in packaging techniques, and 76.6% in digital marketing. These improvements are expected to increase farmers' income by enabling them to sell durable dried lemon products to wider markets. Initial evaluations indicated a high level of satisfaction among the farmers with the program. This program is expected to improve farmers' welfare and economic independence.